Application of Jackson Network Queue Model on Visitor Queue at Population and Civil Registration Service of Batubara District - Maswitha, Maswitha; Sitorus, Syahriol (Ilmu Bersama Center, 2025)
Queues are a common problem in society, queues can occur because the level of service demand is greater than the level of facility capacity to provide services. Jackson network queue is a queue model used to describe a queue system that consists of several interconnected locations or servers, where customers move between locations based on certain rules. Jackson network queue refers to the application of queues to model a service system consisting of several interconnected service stages or locations to increase efficiency and reduce customer waiting time. Data collection was conducted at the Population and Civil Registration Office of Batubara Regency for ten days, the counters studied were the registration counter and the recording counter. The initial queue model was Single Channel-Multi Phase with 1 registration counter and 5 recording counters. The results obtained after applying the Jackson network queue method were that the queue model changed to Multi Channel-Multi Phase by adding workstations and the number of employees at each workstation, for 2 registration workstations, 5 general/regular recording workstations, and 1 special recording workstation for visitors who do not have complete files. The results obtained were that the waiting time for visitors at the registration counter and recording counter was 9 minutes, shorter than before using the Jackson network queue system with a total of 23 minutes. These results can be used as a reference to speed up the waiting time for visitors at the Population and Civil Registration Office of Batubara Regency.